Step
*
1
of Lemma
free-dist-lattice-hom-unique2
1. T : Type
2. eq : EqDecider(T)
3. L : BoundedDistributiveLattice
4. eqL : EqDecider(Point(L))
5. g : Point(free-dist-lattice(T; eq)) ⟶ Point(L)
6. ∀[a,b:Point(free-dist-lattice(T; eq))].  ((g a ∧ g b = (g a ∧ b) ∈ Point(L)) ∧ (g a ∨ g b = (g a ∨ b) ∈ Point(L)))
7. (g 0) = 0 ∈ Point(L)
8. (g 1) = 1 ∈ Point(L)
9. h : Point(free-dist-lattice(T; eq)) ⟶ Point(L)
10. ∀[a,b:Point(free-dist-lattice(T; eq))].  ((h a ∧ h b = (h a ∧ b) ∈ Point(L)) ∧ (h a ∨ h b = (h a ∨ b) ∈ Point(L)))
11. (h 0) = 0 ∈ Point(L)
12. (h 1) = 1 ∈ Point(L)
13. ∀x:T. ((g free-dl-inc(x)) = (h free-dl-inc(x)) ∈ Point(L))
⊢ g = h ∈ (Point(free-dist-lattice(T; eq)) ⟶ Point(L))
BY
{ (FunExt THENA Auto) }
1
1. T : Type
2. eq : EqDecider(T)
3. L : BoundedDistributiveLattice
4. eqL : EqDecider(Point(L))
5. g : Point(free-dist-lattice(T; eq)) ⟶ Point(L)
6. ∀[a,b:Point(free-dist-lattice(T; eq))].  ((g a ∧ g b = (g a ∧ b) ∈ Point(L)) ∧ (g a ∨ g b = (g a ∨ b) ∈ Point(L)))
7. (g 0) = 0 ∈ Point(L)
8. (g 1) = 1 ∈ Point(L)
9. h : Point(free-dist-lattice(T; eq)) ⟶ Point(L)
10. ∀[a,b:Point(free-dist-lattice(T; eq))].  ((h a ∧ h b = (h a ∧ b) ∈ Point(L)) ∧ (h a ∨ h b = (h a ∨ b) ∈ Point(L)))
11. (h 0) = 0 ∈ Point(L)
12. (h 1) = 1 ∈ Point(L)
13. ∀x:T. ((g free-dl-inc(x)) = (h free-dl-inc(x)) ∈ Point(L))
14. x : Point(free-dist-lattice(T; eq))
⊢ (g x) = (h x) ∈ Point(L)
Latex:
Latex:
1.  T  :  Type
2.  eq  :  EqDecider(T)
3.  L  :  BoundedDistributiveLattice
4.  eqL  :  EqDecider(Point(L))
5.  g  :  Point(free-dist-lattice(T;  eq))  {}\mrightarrow{}  Point(L)
6.  \mforall{}[a,b:Point(free-dist-lattice(T;  eq))].    ((g  a  \mwedge{}  g  b  =  (g  a  \mwedge{}  b))  \mwedge{}  (g  a  \mvee{}  g  b  =  (g  a  \mvee{}  b)))
7.  (g  0)  =  0
8.  (g  1)  =  1
9.  h  :  Point(free-dist-lattice(T;  eq))  {}\mrightarrow{}  Point(L)
10.  \mforall{}[a,b:Point(free-dist-lattice(T;  eq))].    ((h  a  \mwedge{}  h  b  =  (h  a  \mwedge{}  b))  \mwedge{}  (h  a  \mvee{}  h  b  =  (h  a  \mvee{}  b)))
11.  (h  0)  =  0
12.  (h  1)  =  1
13.  \mforall{}x:T.  ((g  free-dl-inc(x))  =  (h  free-dl-inc(x)))
\mvdash{}  g  =  h
By
Latex:
(FunExt  THENA  Auto)
Home
Index